Raising critical consciousness in adolescents: an evaluation of the FAIR curriculum - Garcia, Michelle, author; Zimmerman, Toni, advisor; Haddock, Shelley, committee member; Anderson, Sharon, committee member (Colorado State University. Libraries, 2016)
There is some evidence that critical consciousness, sociopolitical awareness and action, may be beneficial to youth development. However, there is a paucity of research throughout the critical consciousness literature evaluating replicable diversity awareness interventions intended to raise levels of critical consciousness. The primary objective of the present study was to evaluate the effectiveness of the FAIR: "Fairness for All Individuals through Respect" program in raising levels of critical consciousness among youth. Critical consciousness was measured using the newly validated Critical Consciousness Scale. No significant differences in critical consciousness scores from pre-test to post-test were found in the intervention group, who participated in the FAIR program, compared to the control group. There were several limitations in the study that prevent the researchers from drawing definitive conclusions.